An intimate distance: women, artists and the body - Betterton, Rosemary.. (Routledge, 1996)
How have women artists taken possession of the female body? What is the relationship between looking and embodiment in art made by women? In a series of original readings of the work of artists from Kathe Kollwitz and Georgia O'Keeffe to Helen Chadwick and Laura Godfrey-Isaacs, Rosemary Betterton explores how women artists have addressed the changing relationship between women, the body and its representation in art. In detailed critical essays that range from the analysis of maternal imagery in the work of German artists at the turn of the century to the unrepresented body in contemporary abstract painting, Betterton argues that women's art practices offer new ways of engaging with our fascinations with and fears about the female body. Reflecting the shift within feminist art over the last decade, An Intimate Distance sets the reinscription of the body within women's art practice in the context of current debates on the body, including reproductive science, maternal subjectivity and the concept of 'body horror' in relation to food, ageing and sex. Drawing on recent theories of embodiment developed within feminist philosophy and psychoanalytic theory, the essays reveal how the permeable boundaries between nature and culture, the female body and technology are being crossed in the work of women artists.
Keywords: 1900-1999; approches et analyses; art contemporain; artistes féministes; arts; corps; cours; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Heterosexual plots and lesbian narratives - Farwell, Marilyn R. (The Cutting edge (New York, N.Y.), 1996)
Qu’est-ce que la littérature lesbienne ? Doit-il contenir des personnages ouvertement lesbiens et les présenter sous un jour positif ? L’auteurice doit-iel être ouvertement (ou secrètement) lesbienne ? Doit-il y avoir un thème lesbien et doit-il être politiquement acceptable ? Marilyn Farwell examine ici le travail d'écrivaines tels qu'Adrienne Rich, Marion Zimmer Bradley, Jeanette Winterson, Gloria Naylor et Marilyn Hacker pour répondre à ces questions. Divisant leurs écrits en deux genres : l'histoire romantique et l'histoire héroïque, ou de quête, Farwell aborde certaines des questions les plus problématiques à l'intersection de la littérature, du sexe, du genre et du postmodernisme. Illustrant comment le conflit générationnel entre les lesbiennes-féministes d’il y a vingt ans et les théoricien.nes queer d’aujourd’hui attise les feux critiques de la théorie lesbienne et littéraire contemporaine, Heterosexual plots and lesbian narratives conclut en plaidant en faveur d’une définition large et généreuse de l’écriture lesbienne.
Keywords: amériques; approches et analyses; arts; discipline; europe; lesbianisme; personnes lesbiennes; postmodernisme; royaume-uni; régions géographiques; états-unis; études littéraires

Postcolonial subjects: Francophone women writers - Green, Mary (University of Minnesota Press, 1996)
Sujets postcoloniaux » est un projet collectif centré sur les questions de langue, d'identité et de voix alors qu'ils abordent les questions de genre, de race, d'ethnicité, de culture et de nation. Les essais critiques présentés ici portent sur les contributions littéraires de femmes contemporaines écrivant en français dont les liens culturels, les identités ethniques et les racines historiques se situent au-delà de l'Hexagone, au-delà de la carte à six faces de la France.
Keywords: approches et analyses; cours; discipline; europe; fem1000; france; francophonie; féminisme décolonial; littérature; premier cycle; ressource en ligne; régions géographiques; thématiques; écriture des femmes*; études littéraires